2022
DOI: 10.1021/acs.accounts.2c00593
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Lipid-Derived Affinity-Based Probes (AfBPs) for Analysis of Lipid–Protein Interactome

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS:Although lipids are not genetically encoded, they are fundamental building blocks of cell membranes and essential components of cell metabolites. Lipids regulate various biological processes, including energy storage, membrane trafficking, signal transduction, and protein secretion; therefore, their metabolic imbalances cause many diseases. Approximately 47 000 lipid species with diverse structures have been identified, but little is known about their crucial ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…These results suggest that AA may regulate lipid metabolism disorders. Lipids are essential metabolites that have many crucial functions 29 . Alterations in hepatic lipid homeostasis may lead to hepatic steatosis, which can progress to steatohepatitis, fibrosis and cirrhosis 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that AA may regulate lipid metabolism disorders. Lipids are essential metabolites that have many crucial functions 29 . Alterations in hepatic lipid homeostasis may lead to hepatic steatosis, which can progress to steatohepatitis, fibrosis and cirrhosis 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipids are essential metabolites that have many crucial functions. 29 Alterations in hepatic lipid homeostasis may lead to hepatic steatosis, which can progress to steatohepatitis, fibrosis and cirrhosis. 30 A previous study also suggested that liver injury caused by anti-tuberculosis drugs may be related to lipid metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology could be further expanded to investigate the roles of other protein residues using established labeling reactions, such as amidation of aspartate and glutamate, or implementation of the many other chemoselective bioconjugation reactions that have been developed in the field of chemical biology. [39][40][41][42][43] https://doi.org/10.26434/chemrxiv-2024-54zn7 ORCID: https://orcid.org/0000-0001-8287-8893 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0…”
Section: How Do We Move Forwardmentioning
confidence: 99%
“…Lipids may be considered primary or secondary metabolites because they can regulate several biological functions within plant cells. Temperature and other environmental factors might influence their biosynthesis [ 48 , 49 ]. Sea fennel exhibited a promising fatty acids profile from both a nutritional point of view, for the presence of unsaturated fatty acids (e.g., oleic, linoleic, and linolenic acid), and an industrial perspective, bearing in mind the relative abundance of petroselinic acid (an antiaging agent) [ 32 , 50 , 51 ].…”
Section: Health-beneficial Compoundsmentioning
confidence: 99%